2015
DOI: 10.1193/011613eqs003m
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Building Motions Using Ratios of the Building's Natural Frequencies and a Timoshenko Beam Model

Abstract: A simple prismatic Timoshenko beam model with soil-structure interaction (SSI) is developed to approximate the dynamic linear elastic behavior of buildings. A closed-form solution with complete vibration modes is derived. It is demonstrated that building properties, including mode shapes, can be derived from knowledge of the natural frequencies of the first two translational modes in a particular direction and from the building dimensions. In many cases, the natural frequencies of a building's first two vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…Note that in accordance with that in other literature, a Timoshenko beam that acts as a surrogate for an actual building can assume the dimensions of that building, including the height and plan dimensions of the building. Therefore, the dimensionless parameter R and the length of the beam L will take on the values of the building under consideration and will not be treated as unknowns.…”
Section: Methodsmentioning
confidence: 60%
“…Note that in accordance with that in other literature, a Timoshenko beam that acts as a surrogate for an actual building can assume the dimensions of that building, including the height and plan dimensions of the building. Therefore, the dimensionless parameter R and the length of the beam L will take on the values of the building under consideration and will not be treated as unknowns.…”
Section: Methodsmentioning
confidence: 60%
“…We believe the reason that may have prevented the third EW mode from being accurately identified from the force vibration test data was the termination of the frequency sweep at 9.7 Hz, which, in turn, fell short in exciting the actual third EW mode. In a recent study, Cheng and Heaton [17] observed the same inconsistency between their findings and Bradford et al [9] and cited the same reason as the source of this inconsistency. • The third NS and torsional modes and the fourth EW mode have not been identified by any study other than the present one.…”
Section: Identification Resultsmentioning
confidence: 81%
“…If the natural frequency ratios of the target building are different from those of a shear beam, then mode shapes from a Timoshenko beam can be adopted when significant flexural response is observed. Cheng and Heaton (2013) developed a Timoshenko beam model with lateral and rotational springs at the base, which simulate the soilstructure interaction effect, to approximate the dynamic linear elastic behavior of the buildings. Mode shapes can be closely approximated by the knowledge of the natural frequencies of the first two translational modes in a particular direction of the building and the building dimensions.…”
Section: Discussionmentioning
confidence: 99%